Pemberdayaan Kelompok PKK Dalam Mewujudkan Pengelolaan Sampah Organik Berkelanjutan Melalui Pelatihan Pembuatan Pupuk Organik Cair - Dyan Hatining Ayu Sudarni; Ahmad Misfa Kurniawan; Candra Putri Winarto; Yansi Fersiana Yudhistira (CV. Multi Kreasi Media, 2026)
Treatment of organic waste management remains a significant challenge in residential communities because waste segregation and utilization are still not optimally implemented. This condition was also identified in Griya Sejahtera Hills Housing Estate, Madiun Regency, where household organic waste was commonly mixed with inorganic waste, increasing the amount of waste transported to the final disposal site. This community service program aimed to improve the knowledge and practical skills of the Family Welfare Empowerment (PKK) members in converting household organic waste into liquid organic fertilizer (LOF) through the application of appropriate technology. The program employed a Participatory Rural Appraisal (PRA) approach combined with a learning by doing method, consisting of observation, socialization, pre-test, training, hands-on practice, mentoring, monitoring, post-test, and evaluation. Twenty PKK members participated in the program. The results demonstrated an improvement in participants' knowledge and practical skills in producing liquid organic fertilizer from household organic waste, as well as increased awareness of sustainable household waste management. Participants were able to independently produce and apply liquid organic fertilizer to home gardens. Furthermore, the program encouraged community commitment to implementing sustainable organic waste management practices, contributing to the reduction of household organic waste and supporting the achievement of the Sustainable Development Goals (SDGs), particularly Goals 11 (Sustainable Cities and Communities), 12 (Responsible Consumption and Production), and 13 (Climate Action).